Caught between competing emotions and tensions - a focus group study exploring experiences of family caregivers of out-of-hospital cardiac arrest survivors. (2nd July 2022) - Rosenkilde, S; Missel, M; Wagner, M; Dichmann, C; Hermansen, A S; Larsen, M K; Joshi, V L; Olsen, A D Z; Borregaard, B
Abstract: Funding Acknowledgements: Type of funding sources: None. Background/Introduction: Being a family member caring for an out-of-hospital cardiac arrest (OHCA) survivor may impact family caregivers' lives due to the sudden onset of the illness and possible secondary cognitive, emotional and physical challenges. However, experiences of caring for an OHCA survivor are sparsely described. Purpose: This purpose of this study was to explore the subjective experiences of family caregivers of OHCA survivors as a means of understanding the potential burden they face. Methods: Using an explorative qualitative approach, six focus group interviews were conducted with a sample of 25 family caregivers of OHCA survivors and analysed using a phenomenological hermeneutic approach inspired by the philosophy of Ricoeur. OHCA survivors and their family caregivers were attenting at a residential rehabilitation course, where the caregivers were interviewed as part of the course. Results: Three themes emerged: i) Feeling unexpectedly alone and invisible; the family caregivers felt an emotional burden that could not be shared – leading to caregiving being a lonely and anxious experience. The family caregiver felt alone with the responsibility of the shared life, ii) Fear of loss; the fear of losing a loved one was a constant companion contributing to the burden of caregiving, and iii) Adjusting to a new everyday life; the family caregivers had difficulties adjusting to living their lives on the basis of the survivors' needs. This often resulted in an existential crisis trying to adapt (Figure 1). Conclusion: The findings of this study illuminate and emphasise the burden experienced by family caregivers and how they can be caught between competing emotions and tensions. The possible caregiver burden following OHCA should be acknowledged. Systematic screening is needed to identify those at risk of high caregiver burden. Further, collaboration with family care givers should be an essential part of post-cardiac arrest care, and interventions to reduce the burden should be tested and implemented as part of the clinical care of OHCA survivors and their families.